DETERMINATION OF SPREADING PARAMETER IN MULTI-VALLEY SEMICONDUCTORS - A. I. Vahanyan
In recent years the thermoelectric properties of materials (specifically solid solutions on the basis of lead [1, 2]), in which conduction band (in the case of n-type semiconductor) or valence band (in the case of p-type semiconductor) has a two-valley structure are often investigated. During the analyses of experimental findings of thermoelectric properties it is very important to have the value of parameter -index of power in the dependence of the free path on the energy, which we’ll briefly denominate spreading parameter.
Keywords: Electronic transport in condensed matter; Physics